Coherent harmonic generation of magnons in spin textures - Guibin Lan; Kang-Yuan Liu; Zhenyu Wang; Fan Xia; Hongjun Xu; Tengyu Guo; Yu Zhang; Bin He; Jiahui Li; Caihua Wan; Gerrit E. W. Bauer; Peng Yan; et al. (Nature Communications)
Abstract Harmonic generation, a notable non-linear phenomenon, has promising applications in information processing. For spin-waves in ferromagnetic materials, great progress has been made in the generation higher harmonics, however probing the coherence of these higher harmonics is challenging. Here, using in-situ diamond sensors, we study the coherent harmonic generation of spin waves in a soft ferromagnet. High-order resonance lines are generated via a microwave input and detected by nitrogen-vacancy (NV) centers in nanodiamonds. The phase coherence of the harmonic spin waves is verified by the Rabi oscillations of the NV electron spins. Numerical simulations indicate that the harmonic generation by microwaves below the ferromagnetic resonance frequency is associated with the nonlinear mixing of spin waves by magnetization structures at the film edge. Our finding of geometry-induced magnon harmonic generation constitutes a new way to generate magnon combs with coherent high-order harmonics and may pave the way for magnon-based information processing and quantum sensing applications.